Distributed Database Systems and Data Replication Algorithms for Intelligent Transport Systems - Janech, Jan; Baca, Tomas; Lieskovsky, Anton; Krsak, Emil; Matiasko, Karol (Communications - Scientific letters of the University of Zilina, 2013)
One can look at the vehicular ad hoc network (VANET) as at the source and storage of information useful for the safety, fluency and comfort of road traffic, which makes it a valuable tool for ITS. Our research is focused on data dissemination in VANET. We perceive the nodes of VANET as the nodes of a distributed database system (DDBS). As such they do not only store data but they also create new data. Normally, in the course of time the data lose their usefulness. The system we designed was tested by means of a computer simulation carried out by the simulation tool AdHocSim.FRI.